Art 1987 AN ANALYSIS OF GOLD SAVINGS THROUGH DIGITAL PLATFORMS FROM THE PERSPECTIVE OF MAQASHID SHARIAH - Maulidina Annisa Dyaz Melati; Subkhan Alimuddin (IAI Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2026)
The rapid growth of digital gold savings platforms in Indonesia namely Tring! by Pegadaian and BYOND by BSI has democratized investment access and reduced entry barriers for middle-to-lower-income communities, necessitating the reactualization of the wealth preservation principle (hifz al-mal) alongside Modern Portfolio Theory (MPT) within contemporary Islamic economic governance. This study analyzes digital gold savings from Maqashid Shariah (hifz al-mal) and MPT perspectives, evaluates akad implementation compliance with DSN-MUI Fatwa instruments, and assesses these platforms as financial inclusion catalysts toward the Indonesia Emas 2045 vision. A qualitative approach was employed, combining empirical analysis of national digital gold platform growth (2023–2026) with a normative review of fiqh muamalah, DSN-MUI Fatwa No. 117/DSN-MUI/II/2018, and modern financial theory. A strong convergence between hifz al-mal and MPT is identified, with digital gold savings demonstrated as effective inflation hedges and inclusive micro-portfolio diversification instruments. The multi- akad structure (murabahah and wadihah)is largely compliant with DSN-MUI Fatwa provisions; however, residual gharar (uncertainty) persists regarding bid-ask spread transparency, underlying asset ownership disclosure prior to akad execution, and custodial fee separation. These platforms constitute strategic financial inclusion instruments supporting household financial resilience; accordingly, regulatory intervention on fee disclosure including maximum spread limits and enhanced sharia financial literacy are recommended to ensure comprehensive maslahah and mitigate gharar.